FDA Approves Omaveloxolone based on Successful Moxie Trial Results for Friedreich’s Ataxia - Review - Kania, Krzysztof; Kania, Joanna; Niekurzak, Karolina; Jędrak, Maciej; Józefiak, Maciej; Sobkiewicz, Piotr (Journal of Education, Health and Sport, 2023)
Introduction: In recent years, the medical community has witnessed a significant breakthrough in the treatment of Friedreich’s Ataxia (FRDA), a rare and debilitating genetic disorder affecting the nervous system. This neurological condition, characterized by progressive muscle weakness, impaired coordination, and cardiomyopathy, has long posed challenges for both patients and healthcare professionals alike. However, there is newfound hope with the recent approval of Omaveloxolone by the U.S. Food and Drug Administration (FDA). Aim of the study: This review article aims to present a detailed summary of the FDA’s approval of Omaveloxolone as a therapeutic option for Friedreich’s Ataxia (FRDA), focusing on the positive results obtained from the MOXIe trial. It covers various aspects of FRDA and explains how Omaveloxolone works as an activator of NRF2, a transcription factor that helps reduce oxidative stress. The MOXIe trial, which examined the safety and effectiveness of Omaveloxolone in FRDA patients, is discussed in detail, including its methodology, primary and secondary goals, and results. Materials and methods: This review was based on available data collected in the PubMed and Google Scholar database, using the key words: FRDA, Friedreich’s Ataxia, Omaveloxolone, RTA 408, NRF2, MOXIe trail. Conclusion: Omaveloxolone has shown significant efficacy in improving neurological function and mFARS scores compared to a placebo in the MOXIe trial. It is well-tolerated with minimal adverse events. Early intervention with Omaveloxolone offers enhanced benefits for managing Friedreich’s ataxia progression.